Likelihood of rising stroke in populace of western India: a case control study - Patel, Kuntal H.; Shroff, Bhavesh D. (International Journal of Research in Medical Sciences, 2023)
Background: Cerebrovascular accident (Stroke) is a non-communicable disease of increasing importance. According to the World Health Organization, 15 million people suffer from stroke worldwide each year. The National Commission on Macroeconomics and Health, India, has estimated 1.67 million stroke cases in India. Due to the increasing prevalence of hypertension, diabetes, dyslipidemia, fast changing lifestyle and re-structuring of population, stroke will be an epidemic in India in the days to come. Few studies have been carried out in developing countries like India. So, this study intended to know the presentation in addition to risk factors, patterns of warning signs and symptoms of stroke in patients admitted to state tertiary care Hospital. Methods: Assuming the power ratio of the number of controls same as numbers of cases specifying values for two sided confidence level 95% and odd ratio 2.15 which was the minimum risk factor in previous study was taken to calculate sample size. Results: After studying of 148 cases of stroke and same controls, we conclude that most common type of stroke is ischemic stroke followed by haemorrhagic stroke. After multivariate analysis we found, modifiable risk factors were mainly mental stress, active and passive smoking, hypertension and obesity. Conclusions: Due to the sheer magnitude, devastating consequences and residual sequelae of the stroke, early intervention in the form of patient education, modification of the lifestyle, non-pharmacological and pharmacological interventions for modifiable risk factors should be an integral aspect of patient care.